Increased QT dispersion in breath-holding spells - (:unkn) unknown (My University, 2004)
Aim: Breath-holding spells are common in infancy and early childhood, and patients are frequently referred to paediatric cardiology clinics for exclusion of heart disease. Recent data reveal subsequent development of epilepsy and neurocardiogenic syncope. Autonomic dysregulation and increased vagal stimulation leading to cardiac arrest and cerebral ischaemia is considered as the cause. Iron deficiency anaemia may be associated with these spells. We studied QT dispersion for the assessment of ventricular repolarization in these patients. Methods: The study group consisted of 19 girls and 24 boys between 3 and 108 mo of age (mean ± SD = 22.7 ± 17.7 mo); and the control group consisted of 13 girls and 12 boys between 3 and 57 mo of age (mean ± SD = 22.9 ± 15.1 mo). QT interval was measured; corrected QT interval (QTc), QT dispersion (QTd) and QTc dispersion (QTcd) were calculated from 12-lead surface electrocardiograms of the patients and the control group. Results: There was no statistically significant difference in terms of QT and QTc intervals between patient and control groups, while QTd and QTcd values were significantly increased in patients with breath-holding spells compared to the healthy children. QT dispersion was 59.5 ± 35.9 ms and 44.8 ± 11.9 ms, respectively, in patients and controls (p < 0.05). QTc dispersion was 102.1 ± 41.9 ms and 79.6 ± 24.6 ms, respectively (p < 0.01). The presence of iron deficiency did not effect the QT and QTc dispersion. Conclusion: QT dispersion is increased in patients with breath-holding spells, and this finding justifies further investigation for rhythm abnormalities and autonomic dysfunction in this patient group.
Keywords: Breath-holding spell; Dysrhythmia; QT dispersion; Syncope